Relatório de Estágio Profissional - À Conquista de um sonho: a época desportiva aos olhos de uma estudante estagiária" - Rita Catarina Nogueira da Costa (2018)
The main purpose was the last and the first step of a dream coming true. It seeks the integration of the pre-service teacher on the exercise of professional life, since that the obstacles, the experiences and the challenges lived in a real context are fundamental for the professional development, as well as for the construction of our own professional identity. The present document - practicum report - pretends to be the mirror of a road traveled by a pre-service teacher (the author), that it seek to relate her biggest passion (futsal) with her biggest dream (being a teacher). About the structure, it is divided in six chapters: I) Press Conference, that frames the academic and sportive routes, as well as the analyses of the competences developed and the initial expectations of the arrival to the school placement; II) Game Field, that reports the framework of the School and the school placement, even as characterize the school and the scholar context where the school placement was made. Additionally, it is still characterized the Tutor of the pre-service teacher, the Cooperating teacher, the pre-service teachers and the two classes that I had the pleasure to work with; III) Pre-Season, that characterizes the whole process of organization and planning; IV) Season, that leads to two areas of performance: Area 1 - Organization and Management of Teaching and Learning, that it's about the practical action, seeking to show the difficulties and challenges faced, as well as strategies used and respective impact on the schoolchildren; Area 3 - Professional Development, where it is revealed the research work and its pertinence among the educational roots; V) Dynamics Develop in the Associative Mass, that remit to Area 2 - Participation in School and Relationship with the Community, in which are presented all the functions and activities realized beyond the programmed in the school component, and IV) Conclusions and future perspectives, that incorporates all the findings retired through the school placement.